Current treatments for non-small cell lung cancer - Guo, Qianqian; Liu, Liwei; Chen, Zelong; Fan, Yannan; Zhou, Yang; Yuan, Ziqiao; Zhang, Wenzhou (Frontiers in Oncology, 2022)
The mortality of lung cancer is surprising, even though the development of different treatments and diagnosis methods. Besides, non-small cell lung cancer (NSCLC) takes a big majority of the lung cancer patients. Therefore, it’s important to review the current treatments of NSCLC in the clinic and pre-clinic. In this review, we list the current diagnosis and therapy (such as chemotherapy, chemoradiotherapy, targeted therapy, antiangiogenic therapy, immunotherapy, and combination therapy) for the NSCLC, which maybe could provide a guidance for the clinic.